Islamic movements in India: moderation and its discontents - Emmerich, Arndt (Royal Asiatic Society books, 2019)
Introduction; 1 Islamic Movements and the Secular State in India; 2 Muslim Citizenship Politics and the Popular Front of India; 3 Framing Muslim Victimhood: The Politics of Grief and Protection; 4 Hindu Self-Defence against Muslim Troublemakers; 5 Islamic Pragmatism and Legal Education: Appeal of the Popular Front of India; 6 Value Politics, Illiberal Agendas and Modernity in India; 7 Conclusion -- Has Secular Politics Failed?